2019
DOI: 10.1103/physrevd.99.016014
|View full text |Cite
|
Sign up to set email alerts
|

Flavor-energy uncertainty relations for neutrino oscillations in quantum field theory

Abstract: In the context of quantum field theory, we derive flavor-energy uncertainty relations for neutrino oscillations. By identifying the non-conserved flavor charges with the "clock observables", we arrive at the Mandelstam-Tamm version of time-energy uncertainty relations. In the ultra-relativistic limit these relations yield the well known condition for neutrino oscillations. Ensuing non-relativistic corrections to the latter are explicitly evaluated. The analogy among flavor states and unstable particles and a n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 46 publications
(50 reference statements)
3
48
0
Order By: Relevance
“…It was recently pointed out [36] that flavor neutrino states share a common feature with unstable particles, in the sense that only their energy (mass) distribution has a physical meaning and the width of this distribution is related to the inverse of the oscillation length which can be again deduced from time-energy uncertainty relation [36,37]. Furthermore, the latter result was recently generalized, in a quantum mechanical context, to stationary curved spacetimes [38].…”
Section: Introductionmentioning
confidence: 96%
“…It was recently pointed out [36] that flavor neutrino states share a common feature with unstable particles, in the sense that only their energy (mass) distribution has a physical meaning and the width of this distribution is related to the inverse of the oscillation length which can be again deduced from time-energy uncertainty relation [36,37]. Furthermore, the latter result was recently generalized, in a quantum mechanical context, to stationary curved spacetimes [38].…”
Section: Introductionmentioning
confidence: 96%
“…Our key finding is that the vacuum state, responsible for dynamical mixing generation, yields the same condensate structure of the flavor vacuum as known from the study of neutrino oscillations, cf., e.g., Refs. [7,8,11,22]. In particular, we have shown that in order to dynamically generate mixing, within our class of models, the classical residual symmetry U (1) V × U (1) m V that responsible for the mixing must be anomalous (only U (1) V symmetry survives quantization), on the account of the flavor vacuum condensate.…”
Section: Conclusion and Discussionmentioning
confidence: 75%
“…We finally point out that recently [35], the use of flavor states led to the interpretation of flavor neutrinos as unstable particles, which periodically decay into different neutrino species. This view is also compatible with the formal statement, based on the study of Schwinger-Dyson equations, according to which flavor neutrinos can be formally thought as single-particle bound states, i.e.…”
Section: Discussionmentioning
confidence: 92%
“…The Lagrangian L is invariant under the global U (1) transformations ν → e iα ν and l → e iα l leading to the conservation of the total flavor charge Q tot l corresponding to the total leptonnumber conservation [15,35]. This can be written in terms of the flavor charges for neutrinos and charged leptons [27]…”
Section: Flavor Charge Conservation In the Vertexmentioning
confidence: 99%